PHILOSOPHICAL BASIS OF IMAGOLOGICAL IMPLICATIONS OF SOCIO-CULTURAL COMPONENT IN CHINESE FLORAL LYRICS - Гуль, Александра (Літературний процес: методологія, імена, тенденції, 2018)
The article outlines the influence of the ancient Chinese philosophic postulates on the formation of worldview picture of the Tianxia citizens. The emphasis is placed on floral images, typical for Chinese lyrics, enriched and grown upon the traditions of Confucianism, Daoism and Buddhism. The article is aimed to reveal the symbolic contents of floral motifs and images, running through Chinese poetry, considering the selectivity of images. Appealing to the images of Chinese poetry, the article underlines the influence of Chinese philosophy on the formation of language poetics, this very fact has been observed by sinologists-literary scholars: Shi Han, Kobzev A. I., contemporaries — Shekera Ya. V., Kolomiyets N. V., Murashevych K. G. The article addresses the floral images, known in China as “the three friends of cold winter”, “the four cardinal virtues”, “the four emperors”. Special focus is made on the cardinal virtues, which are behind the floral images, with the focus on personification; on identifying the male principle (Yang) and the female principle (Yin), being primarily put into these plants. The article reveals the symbolization of floral images, giving not only Eastern-philosophical concept, but representing the inner world of the poet-creator, thus, making a visual space, which will help to understand the role and place of a person in Chinese social environment.